2018
DOI: 10.1002/ejoc.201800556
|View full text |Cite
|
Sign up to set email alerts
|

Organic Synthesis without Conventional Solvents

Abstract: Organic synthesis without an organic solvent is still the exception. In this microreview, we discuss and compare different synthetic methods that proceed in the absence of conventional organic solvents. This includes solvent‐free methods in solids (mechanochemistry and solid‐state photochemistry), and in neat liquids (thermal and photocatalytic), as well as the application of unconventional solvents, such as ionic liquids and deep‐eutectic solvents. The different approaches are briefly introduced and examples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 195 publications
(359 reference statements)
0
30
0
3
Order By: Relevance
“…Photocatalysis in the solid-state was reported by the Kçnig group [84] in 2016, who used arod mill reactor in which at hin layer of as olid reaction mixture is sheared under irradiation. To achieve photocatalysis while ball milling, Hernµndez used ap oly(methylmethacrylate) jar wrapped by as trip of blue-or green-emitting light-emitting diodes to perform borylation of diazonium salts mediated by Eosin Y.…”
Section: Mechanochemical Photocatalytic Reactionsmentioning
confidence: 99%
“…Photocatalysis in the solid-state was reported by the Kçnig group [84] in 2016, who used arod mill reactor in which at hin layer of as olid reaction mixture is sheared under irradiation. To achieve photocatalysis while ball milling, Hernµndez used ap oly(methylmethacrylate) jar wrapped by as trip of blue-or green-emitting light-emitting diodes to perform borylation of diazonium salts mediated by Eosin Y.…”
Section: Mechanochemical Photocatalytic Reactionsmentioning
confidence: 99%
“…deep eutectic solvents (DES) 71 and Natural Deep Eutectic Solvents (NADES) 72 , prepared from natural products with fewer EHS issues is increasing, and these solvents are showing some surprising reactivity. 73,74 The application of chemo-and biocatalysis is aligned to green chemistry principles 75 and can be more compatible with the "greener" solvent classes. The use of nano-particulate metal catalysts is emerging in the field of chemo-catalysis and applied to reactions commonly used in API synthesis.…”
Section: The Role Of Green Solvents In Chemical Manufacturingmentioning
confidence: 99%
“…24,25 Finally, while the practical utility of ionic liquids is sometimes limited by their expense (uorinated anions being particularly problematic in this context), 26,27 numerous DESs can be prepared from inexpensive, commodity chemicals. 28 These favorable characteristics have led to a range of applications in a variety of elds, including synthesis, 29,30 catalysis, 31 and chemical analysis, 32 among others. While the vast majority of deep eutectic solvents described to date are hydrophilic, 33,34 recent work has shown that a hydrophobic DES (designated hereaer as an HDES) can be readily obtained by combining menthol [35][36][37][38] or an appropriate quaternary ammonium halide [39][40][41] with a longchain carboxylic acid.…”
Section: Introductionmentioning
confidence: 99%